PENERAPAN BATUK EFEKTIF PADA PASIEN BRONKITIS DENGAN KETIDAKEFEKTIFAN BERSIHAN JALAN NAPAS: THE APPLICATION OF EFFECTIVE COUGHING IN PATIENTS WITH BRONCHITIS WITH INEFFECTIVE AIRWAY CLEARANCE - Kusyani, Asri (LPPM STIKes Bahrul Ulum Jombang, 2025)
Bronchitis is an infectious disease of the respiratory tract that attacks the bronchi caused by bacterial or viral infections that result in the accumulation of excess secretions in the bronchi, resulting in ineffective airway clearance. The aim of this study is to be able to carry out nursing care for bronchitis clients with ineffective airway clearance through effective cough interventions. This study uses a case study method, which is carried out on 2 bronchitis clients. Data collection through interviews, observations and physical examinations. Data analysis by means of data collection, evaluation and conclusion of research ethics. The results of respondent 1's assessment cough for 5 days with white mucus. General condition: GCS 4-5-6 weak, cough visible. Both lung sounds are loud. There are additional rhonchi sounds. Blood pressure 120/80 mmHg. Pulse 98x/minute. Respiration 24x/minute. SPO2 98%. Temperature 36.3°C. Respondent 2 coughed up mucus for 4 days General condition: GCS weak: 4-5-6, shortness of breath and cough were visible, there was use of accessory respiratory muscles, both lung sounds were loud, there were additional rales, prolonged expiratory phase, tachypnea, blood pressure 110/80 mmHg, pulse, 62/minute. 94%, temperature 38.5°C. Implementation was carried out for 3 days, which was to provide effective coughing to remove secretions. Assessment on the third day showed that client 1 was no longer coughing, client 2 was no longer coughing and was no longer short of breath. The problems of both clients were resolved, the intervention provided can be carried out every day on bronchitis sufferers in the hospital or at home because its implementation is free, so it is more effective and efficient.